PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN ORGANISASI, DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA KOPERASI SIMPAN PINJAM (KSP) DANADYAKSA DI TABANAN - I Putu Bayu Sanjaya; Ida Bagus Udayana Putra; Ni Kadek Sioaji Yamawati (Warmadewa Management and Business Journal (WMBJ), 2022)
Human resources are assets for the company which if managed will result in performance for the company which will certainly be profitable for the company. Employee performance is one of the most important things in the company, factors that affect employee performance such as transformational leadership style, organizational commitment, and work discipline must always be considered. The purpose of this study was to determine the effect of transformational leadership style, organizational commitment and work discipline on employee performance at the Danadyaksa Savings and Loans Cooperative (KSP) in Tabanan. The number of respondents in this study were 32 people. The data analysis technique used is quantitative analysis, classical assumption test, multiple linear regression analysis, F test and t test. F-test results obtained Fcount > F-table with sig. 0.003 < 0.05, this means that transformational leadership style, organizational commitment and work discipline have a positive and significant effect on employee performance at the Danadyaksa Savings and Loans Cooperative (KSP) in Tabanan.